2012
DOI: 10.1002/ange.201105638
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of β‐Amyloid‐Dependent Synaptic Dysfunctions

Abstract: Mehr Information über Alzheimer: Die Konformation einer toxischen oligomeren β‐Amyloid(Aβ)‐Struktur wurde mit NMR‐Spektroskopie aufgeklärt (siehe Bild). Die Messungen belegen, dass ein N‐terminaler β‐Strang entscheidet, ob Oligomere oder Protofibrillen gebildet werden. Durch Eingriff am N‐Terminus des Peptids können neuronale Aβ‐abhängige Fehlfunktionen ausgeschaltet werden. Alzheimer kann somit auf struktureller Basis verstanden werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 27 publications
8
36
0
2
Order By: Relevance
“…We propose that this more extended conformation of the N-terminal region of Aβ may form the structural basis for the enhanced stability of phosphorylated Aβ oligomers. This is in agreement with a recent report showing that the disruption of local extended conformation through S8P mutagenesis leads to selective destabilization of Aβ oligomers 37 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We propose that this more extended conformation of the N-terminal region of Aβ may form the structural basis for the enhanced stability of phosphorylated Aβ oligomers. This is in agreement with a recent report showing that the disruption of local extended conformation through S8P mutagenesis leads to selective destabilization of Aβ oligomers 37 .…”
Section: Discussionsupporting
confidence: 94%
“…Several lines of evidence attribute an important role for aggregation of Aβ to its N-terminal region 37 38 39 40 . The results from our MD simulation suggested that the high capacity of phosphate groups to act both as the donor and acceptor of hydrogen bonds can lead to the formation of a rich network of hydrogen bonds in the N-terminal region and significantly diminishes backbone dynamics in phosphorylated Aβ aggregates ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The N‐terminal region of Aβ peptides is highly important for its aggregation and toxicity . We therefore decided to investigate the impact of N‐terminal elongation on the aggregation behavior of Aβ peptides using a set of biophysical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that KW1 expression specifically affects Aβ(1-40)-transgenic animals was highly surprising, given that it had previously been shown to antagonize Aβ(1-40) oligomer induced neurotoxicity (Figure  5A,B), as measured by the ability of preformed oligomers of Aβ(1-40) to disrupt synaptic plasticity and LTP in cultured murine brain slices [29,37,46]. An obvious contrast between the fly model described here, and previous in vitro work is that KW1 is produced in the brain of the fly concomitantly with Aβ(1-40) peptide and is present during fibril or oligomer formation (Figure  5C).…”
Section: Resultsmentioning
confidence: 99%
“…Fibrils were formed in vitro by incubation of pure peptide at 1 mg/ml concentration in 50 mM sodium borate buffer, pH 9.0, for 5 days at room temperature. Oligomers were prepared by dissolving pure peptide at 2.5 mg/ml concentration in 100% 1,1,1,3,3,3-hexafluoro-2-propanol [37]. After incubation for 15 min at room temperature, the solution was diluted 10-fold with H 2 O and further incubated for 15 min.…”
Section: Methodsmentioning
confidence: 99%